Applied Biological Chemistry - Lee, Hojoung; Kim, In Seon.; Lee, Hoi-Seon.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer.)
Applied Biological Chemistry aims to promote the interchange and dissemination of scientific data among researchers in the field of agricultural and biological chemistry. The journal covers biochemistry and molecular biology, medical and biomaterial science, food science, and environmental science as applied to multidisciplinary agriculture.
Keywords: Industrial microbiology; Bioorganic chemistry; Biology$1 (BTechnique.s; Industrial Microbiology; Bioorganic Chemistry; Biological Techniques